2000
DOI: 10.1161/01.hyp.35.1.329
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Associated With Tissue-Specific Activation of Renal Angiotensin-Converting Enzyme In Vivo

Abstract: Abstract-In the C57BL/6J mice model, we investigated whether obesity affects the function or expression of components of the tissue renin-angiotensin system and whether endothelin (ET)-1 contributes to these changes. ACE activity (nmol ⅐ L His-Leu ⅐ mg protein Ϫ1 ) was measured in lung, kidney, and liver in control (receiving standard chow) and obese animals treated for 30 weeks with a high-fat, low cholesterol diet alone or in combination with LU135252, an orally active ET A receptor antagonist. ACE mRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
104
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 54 publications
9
104
2
Order By: Relevance
“…Indeed, Nielsen et al 27 showed a significant correlation between the vascular response to Ang II and the plasma palmitate concentration. In terms of Ang II-forming activity from Ang I, Barton et al 28 showed the activation of renal Ang-converting enzyme activity in obese animals. Increased FFA levels, however, did not alter the FBF response to either Ang I or II in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Nielsen et al 27 showed a significant correlation between the vascular response to Ang II and the plasma palmitate concentration. In terms of Ang II-forming activity from Ang I, Barton et al 28 showed the activation of renal Ang-converting enzyme activity in obese animals. Increased FFA levels, however, did not alter the FBF response to either Ang I or II in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, obesity potentiated angiotensin II-induced vasoconstriction in aortic but not in carotid arterial rings in vitro, indicating that the vascular effects of angiotensin II are site specific in this model of experimental obesity [Barton et al, 2000].…”
Section: Obesity-related Sympathetic Activation and Vascular Remodelingmentioning
confidence: 83%
“…In addition, Nielsen et al [2004] studied obese subjects with family history of hypertension, which could per se potentiate the vasoconstrictor effect of angiotensin II. Furthermore, diverse vascular beds may respond differently to angiotensin II stimulation, as demonstrated in experimental models of obesity [Barton et al, 2000].…”
Section: Obesity-related Sympathetic Activation and Vascular Remodelingmentioning
confidence: 99%
“…16 PPARa is also well known as a determinant of the development of hypertension and renal damage, especially in AT-II-induced hypertensive rats. 21,23,24,30 Induction of the renal expression of CYP4A enzymes in the kidney using fibrate compounds has been reported to lower BP in SHR, stroke-prone SHR and Dahl salt-sensitive rats. 31,32 We found the inverse pattern of PPARa expression in kidneys of WKY-HF rats compared with that in SHR-HF animals.…”
Section: Discussionmentioning
confidence: 99%